Aliya madrasah students motivation for learning English in Bangladesh - Md Mahbuber Rahman, Abu Rashed; Jalaluddin, Ilyana; Mohd Kasim, Zalina; Darmi, Ramiza (Selcuk University, 2021)
The purpose of the study was to investigate the factors and level of motivation for learning English among Aliya madrasah students in Bangladesh. The study also explored to find out the differences in students motivation for learning English as L2 based on gender of the students, parents education level, and monthly family income of their parents. The data for this study was collected via questionnaire survey among 300 participants selected through simple random method from six Aliya madrasahs. Adapted Attitude Motivation Test Battery (AMTB) questionnaire of Gardner (1985, 2004) was employed in this study. The data for this study was analysed quantitatively such as descriptive statistics, independent sample T-test, and one-way ANOVA using (SPSS) version 25 as statistical tool. The results showed that most of the students were instrumentally motivated for learning English than integrative motivation and their motivation level was high. The analysis also showed that there was statistically significant difference in their motivation for learning English based on their parents monthly family income, and their parents education level. However, the result revealed no significant difference in their motivation for learning English with regard to gender. A On the basis of the results, the implications were discussed concerning students motivation for learning English.